To invest or not to invest the business Angel´s dilemma - Oscar Arroyo-Revilla; Cayetano Medina-Molina; Carlos Bellón Núñez-Mera; Noemí Pérez-Macías (Journal of Innovation & Knowledge)
Business Angels (BAs) are pivotal in early-stage funding for entrepreneurship. This study explores the factors influencing BA investment decisions. We propose a theoretical model based on signaling theory to assess the impact of signals about the quality of entrepreneurs and projects on investment assessments and decisions. Using qualitative comparative analysis (QCA) on 88 survey responses from BAs in Spain, we identify the signal combinations influencing both preliminary evaluation and final investment decisions.Our findings highlight two key insights. First, both entrepreneurial and project-related factors are crucial in assessing opportunities and making investment decisions, with the entrepreneur's personal characteristics, particularly trust, being vital. Second, we examine the varying configurations of evaluation criteria used by BAs at different investment stages, revealing that selection criteria evolve from initial screening to the final decision, challenging the previously believed compensatory decision model.This article enhances the understanding of investment criteria asymmetry, providing valuable insights for the entrepreneurial ecosystem to close funding rounds effectively and revealing significant heterogeneity in BAs investment strategies, thus confirming the concept of equifinality.